2013
DOI: 10.2478/prolas-2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Sawfly Populations (Hymenoptera, Symphyta: Hoplocampa Spp.) In Plum And Apple Orchards Using Visual Traps

Abstract: The investigation of Hoplocampa minuta (Christ, 1791) (black plum sawfly), Hoplocampa flava (Linné, 1760) (yellow plum sawfly) and Hoplocampa testudinea (Klug, 1816) (apple sawfly) populations using white sticky traps Rebell®bianco was carried out in conventionally and organically managed apple and conventionally managed plum orchards of the Institute of Horticulture of Lithuanian Research Centre for Agriculture and Forestry in 2010 and 2011. Temperature sums for predicting sawfly spring emergence were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Some studies indicated highly variable damage levels by secondary apple pests like apple sawfly (Tamosiunas et al, 2013;Tamošiūnas et al, 2014;2015) or green apple aphids (Raudonis et al, 2010) on different apple cultivars in the same orchard, pests were successfully controlled in our experiment by sustainable plant protection system. The activity of apple codling moth adults was determined during all seasons of our investigations (Table 3).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Some studies indicated highly variable damage levels by secondary apple pests like apple sawfly (Tamosiunas et al, 2013;Tamošiūnas et al, 2014;2015) or green apple aphids (Raudonis et al, 2010) on different apple cultivars in the same orchard, pests were successfully controlled in our experiment by sustainable plant protection system. The activity of apple codling moth adults was determined during all seasons of our investigations (Table 3).…”
Section: Resultsmentioning
confidence: 72%
“…mancozeb (2.0) -pheromone traps for insects pheromone traps for insects pheromone traps for insects measure based on a mean number of insects captured per trap during a particular time interval (Tamosiunas et al, 2013;Tamošiūnas et al, 2014). Insecticides were applied when the density of pests was reaching the threshold of harmfulness.…”
Section: Methodsmentioning
confidence: 99%